Target language, collaborative learning and autonomy - Macaro, Ernesto (Modern languages in practice, 1997)
"This book explores the relevance that second language research has for the secondary foreign language classroom. It analyses the concept of teaching and learning exclusively through the target language. This concept is then related to two current pedagogical tendencies: peer collaboration and learner autonomy."--Jacket